Rituximab in treatment of a patient with granulomatosis with polyangitis - a case report - Bojadjioska, Maja; Guchev, Filip; Antova, Dubravka; Karadzova Stojanovska, Anzhelika; Vidinikj, Sonja; Damjanovska Krstikj, Ljubinka; Sandevska, Emilija; Vasilevska, Ana; Petrova, Sanja; Tofiloska, Valentina; Curakova Ristovska, Elena; Vejseli, Ron (Македонско лекарско друштво = Macedonian medical association, 2023)
ANCA-associated vasculitis (AAV) is a necrotizing vasculitis with few or no immune deposits that can affect predominantly small vessels. It can affect vessels in every organ and tissue of the body; the clinical manifestations of the disease are extremely variable. B-cells are of major importance in the disease pathogenesis as precursors of ANCA-producing plasma cells and, possibly, also as antigen-presenting and cytokineproducing cells. Therefore, rituximab, a monoclonal antibody drug causing partial B-cell depletion, has emerged as a powerful option in the treatment of AAV such as granulomatosis with polyangiitis. We present the case of a 25-year-old female diagnosed with granulomatosis with polyangiitis and treated with rituximab and high-dose corticosteroids.
Keywords: ANCA; vasculitis; rituximab; treatment; remission